A Radiologist's Perspective on Treatment-Related Pseudoprogression: Clues and Hues - Chakrabarty, Nivedita; Mahajan, Abhishek; Baheti, Akshay D.; Choudhari, Amit; Patil, Vasundhara; Popat, Palak; Unde, Himangi (Indian Journal of Medical and Paediatric Oncology, 2022)
Pseudoprogression refers to the initial apparent increase in tumor burden observed on imaging after cancer therapy, with subsequent delayed response to the same treatment, thus giving a false initial appearance of disease progression. It is essential to differentiate pseudoprogression from true progression to prevent the patients from getting deprived of the benefits of their ongoing cancer therapy owing to their early withdrawal. It also affects their recruitment for clinical trials. Pseudoprogression, albeit uncommon, has been observed after various types of cancer therapy; however, this phenomenon has gained momentum of late due to the emergence of immunotherapy for the treatment of various malignancies. Besides immunotherapy, pseudoprogression has predominantly been of concern in a few patients after radiation therapy for brain tumors and metastasis, after molecular targeted therapy for a variety of tumors, and after chemotherapy in metastatic bone lesions. This article reviews the available data on imaging of pseudoprogression from various types of cancer therapies, highlighting ways to suspect or identify it on imaging.
Keywords: pseudoprogression; immunotherapy; radiation therapy; targeted therapy